Effects of Particulate Matter and Its Chemical Constituents on Elderly Hospital Admissions Due to Circulatory and Respiratory Diseases - Ferreira, Tatiane Morais (Int J Environ Res Public Health, 2016)
Various fractions of particulate matter have been associated with increased mortality and morbidity. The purpose of our study is to analyze the associations between concentrations of PM(2.5), PM(2.5–10), PM(10) and their chemical constituents (soluble ions) with hospital admissions due to circulatory and respiratory diseases among the elderly in a medium-sized city in Brazil. A time series study was conducted using Poisson regression with generalized additive models adjusted for confounders. Statistically significant associations were identified between PM(10) and PM(2.5–10) and respiratory diseases. Risks of hospitalization increased by 23.5% (95% CI: 13.5; 34.3) and 12.8% (95% CI: 6.0; 20.0) per 10 μg/m(3) of PM(2.5-10) and PM(10), respectively. PM(2.5) exhibited a significant association with circulatory system diseases, with the risk of hospitalization increasing by 19.6% (95% CI: 6.4; 34.6) per 10 μg/m(3). Regarding the chemical species; SO(4)(2−), NO(3)(−), NH(4)(+) and K(+) exhibited specific patterns of risk, relative to the investigated outcomes. Overall, SO(4)(2−) in PM(2.5–10) and K(+) in PM(2.5) were associated with increased risk of hospital admissions due to both types of diseases. The results agree with evidence indicating that the risks for different health outcomes vary in relation to the fractions and chemical composition of PM(10). Thus, PM(10) speciation studies may contribute to the establishment of more selective pollution control policies.